MEDIA CONVERGENCE USING LOCAL FOOD (TINUTUAN) TO IMPROVE MOTHERS’ KNOWLEDGE, ATTITUDES, AND BEHAVIORS FOR STUNTING PREVENTION IN KEMA, NORTH MINAHASA - Manoppo, Mutiara Wahyuni; Padaunan, Ellen (Fakultas Keperawatan, Universitas Klabat, 2025)
Stunting is a health issue in children that can be avoided by providing appropriate nutrition intervention and improving nutritious locally sourced meals. Manado porridge, known as tinutuan, is a nourishing traditional cuisine from North Sulawesi, Indonesia. It can be used as a supplementary diet to reduce stunting in children under the age of five. However, due to a lack of information among mothers, tinutuan is primarily taken by adults. Media Convergence is an effective way to increase knowledge, attitude, and behavior related to stunting prevention. The purpose of this study was to analyze the effect of media convergence based on local foods on mothers' knowledge, attitudes, and behaviors of stunting prevention in children under the age of five. A quasi-experimental design with a control group, pre, and posttest was used. The purposive sampling technique was used to recruit 30 respondents. The intervention was carried out by education using media convergence of booklet dan videos that contain about stunting and how to prevent it using locally sourced food, also how to cook the tinutuan. Mann-Whitney tests were used to analyze the effect on the treatment group before the intervention. The result shows that there is significant effect of media convergence based on local foods on mothers' knowledge, attitudes, and behaviors of stunting prevention (p < 0.005). Stunting adalah masalah kesehatan pada anak-anak yang dapat dicegah dengan memberikan intervensi gizi yang tepat dan meningkatkan kualitas makanan bergizi yang berasal dari pangan lokal. Bubur Manado, yang dikenal sebagai tinutuan, adalah masakan tradisional bergizi dari Sulawesi Utara, Indonesia. Bubur ini dapat digunakan sebagai makanan tambahan untuk mengurangi stunting pada anak di bawah usia lima tahun. Namun, karena kurangnya informasi di kalangan ibu, tinutuan umumnya dikonsumsi oleh orang dewasa. Konvergensi media merupakan cara efektif untuk meningkatkan pengetahuan, sikap, dan perilaku terkait pencegahan stunting. Tujuan studi ini adalah menganalisis pengaruh konvergensi media berbasis pangan lokal terhadap pengetahuan, sikap, dan perilaku ibu dalam pencegahan stunting pada anak di bawah usia lima tahun. Desain quasi-eksperimental dengan kelompok control menggunakan pretest dan posttest. Teknik purposive sampling digunakan untuk merekrut 30 responden. Intervensi dilakukan melalui edukasi menggunakan konvergensi media berupa booklet dan video yang berisi informasi tentang stunting dan cara mencegahnya menggunakan makanan lokal, serta cara memasak tinutuan. Uji Mann-Whitney digunakan untuk menganalisis pengaruh pada kelompok perlakuan sebelum intervensi. Hasil menunjukkan bahwa terdapat pengaruh yang signifikan dari konvergensi media berbasis makanan lokal terhadap pengetahuan, sikap, dan perilaku ibu dalam pencegahan stunting (p < 0.005).